Filosofi Frase “Kuserahkan Kepada Iblis” 1 Timotius 1:20 dalam Upaya Melawan Ajaran Sesat di GMAHK Limputong Papar Sabah Malaysia - Baninus, Rayner Dino; Hutagalung, Stimson (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study examines the philosophical analysis of the phrase “I hand them over to Satan” based on 1 Timothy 1:20 in the effort to combat heretical teachings in the Seventh-day Adventist Church of Limputong, Papar. The study explores the philosophical meaning of the phrase “I hand them over to Satan” in 1 Timothy 1:20, the influence of the congregation’s understanding of this phrase on their attitude toward heretical teachings, and its relevance in the context of the modern church. The research employs a qualitative method through literature studies and surveys. The findings indicate that this phrase represents a form of church discipline aimed at restoration, with the goal of leading wayward individuals to repentance. Church leaders and theologians interpret this phrase as a disciplinary action with a restorative dimension, incorporating counselling, theological education, and spiritual recovery, following the steps outlined in Matthew 18:15-17. Practical steps in combating heretical teachings include enhancing biblical understanding, conducting Bible seminars, issuing pastoral warnings, and employing a loving approach.